ERS International Congress 2022: highlights from the Epidemiology and Environment Assembly - James G.H. Parkin; Laura Delgado-Ortiz; Rosalie Delvert; Manosij Ghosh; Aliki Korkontzelou; Sarang Patil; Marine Savouré; Mateusz Jankowski; Orianne Dumas (ERJ Open Research, 2023)
In this article, early career members of the Epidemiology and Environment Assembly of the European Respiratory Society summarise a selection of five sessions from the Society's 2022 International Congress, with a focus on areas of specific interest for the Assembly, i.e. epidemiology and risk factors of respiratory diseases in both children and adults. Topics covered include the characterisation of obstructive respiratory diseases, their comorbidities and their evolution, with novel insight from large cohorts. The importance of early-life factors in respiratory health was also emphasised, including maternal exposures and habits during pregnancy. As smoking behaviours have changed following the introduction of e-cigarettes and heated tobacco products, research remains very active to determine the health consequences and predictors of these novel uses, especially in teenagers. The impact of environmental and occupational exposures on respiratory health remained a major topic of the congress, with a focus on emerging risk factors such as landscape fire smoke, non-exhaust particles and nanoparticles. Regarding workplace exposures, old and novel causes of occupational asthma and rhinitis were discussed.